The Surgical Outcomes of Diaphyseal Fractures of Radius and Ulna treated by Plate and Screws Fixation in Vietnam - Dung Tran Trung; Khanh Trinh Le; Tuyen Nguyen Trung; Binh Nguyen Duc; Lam Tran Quoc; Manh Nguyen Huu; Phuong Nguyen Huy; Nam Vu Tu; Hieu Pham Trung (Open Journal of Trauma - Peertechz Publications, 2017)
Objectives: 1) Study the clinical and radiographic characteristics of both bones forearm fractures in adults. 2) Evaluate the surgical outcomes of plate and screws fixation for these fractures. Material and methods: This retrospective study included 66 cases of both bones forearm fractures who were treated by open reduction and internal fixation (ORIF) with plate and screws at Viet Duc Hospital and Hanoi Medical University Hospital between January 2010 and June 2013. Results: The average age of the patients was 34.73 ± 13.54; the ratio of men to women was 2.5/1;Traffic accident was the major mechanism of injury; fractures of middle third of radius and ulna were the most common, accounting for 48.49% of cases. Fractures in left-side were more than right. The surgical outcomes were excellent in 75.8% of cases, satisfactory in 18.2% and unsatisfactory in 6%. There were no failures. Conclusion: Plate and screws fixation of both bones forearm fractures had good results.